Eco-friendly Management of Alternaria Blight in Brassica juncea - and R.L. MEENA, P.D. MEENA*, C. CHATTOPADHYAY (Indian Phytopathology, 2008)
Application of 1 per cent (wlv) aqueous bulb extract of Allium sativum at 45 and 75 days after sowing (DAS) resulted in lowest blight severity on leaves and pods and highest seed yield. Though disease severity in the treatment was at par with that in mancozeb, application of plant extract resulted in significantly higher seed yield compared to mancozeb in 2002-03 and 2003-04. However, application of treatments only once at 75 DAS, GR isolate of Trichoderma harzianum at 45 and 75 DAS, A. sativum 45 DAS + T. harzianum 75 DAS and T. harzianum 45 DAS + A. sativum 75 DAS during 2002-03 resulted in seed yield at par with application of mancozeb at 45 and 75 DAS. Bulb extract of A. sativum at 45 and 75 DAS was found significantly superior over all the treatments in increasing seed yield while being at par with mancozeb at 45 and 75 DAS. Foliar spray by A. sativum was also economical as it provided better incremental benefit cost ratio.